Investigative computer forensics : the practical guide for lawyers, accountants, investigators, and business - Laykin, Erik (John Wiley, 2013)
"Having worked with Erik on some of the most challenging computer forensic investigations during the early years of this industry's formation as well as having competed with him earnestly in the marketplace ... I can truly say that Erik is one of the unique pioneers of computer forensic investigations. He not only can distill complex technical information into easily understandable concepts, but he always retained a long, term global perspective on the relevancy of our work and on the impact of the information revolution on the social and business structures of tomorrow."--The Foreword by James Gordon, Managing Director, Navigant Consulting, Inc.